(3QSGdI aj Ndb GdCYeGds - (3LdGd GdOjf eMeO Hf CSYO GdUOjbj GdOhGfj, GdOhGfj,J (B918 (3g` s ((3Cejf Hf NjQ Gddg GdYeQi GdNWjH s)
(3ChdgG (B:s
(3CeG HYO HMeO Gddg aJGM GdbdhH abO SCdfi GdCN ai GdOjf SYO GdOjf eMeO GdCSJQGHGOi ai HYV GdCSaGQ hCfG eSJha Cf CcJH dg eG MVQfi ai GdhbJ HeSCdg Ndb GdCYeGd s
(3BNQgG (B:s
(3abGd fhQ jTQb ef UHM GdCRd adjhM Ydi gjGcd GdJhMjO EfGQg abGd ROfi ajg HjGfkG abGd GWai GdSQGL abO WdY GdUHM JeJ GdQSGdI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B11s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B32s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeOQSI GdCMeOjI (B_ (3GdehUd (B(115) s
Keywords: (3GdeLGejYs